2006
DOI: 10.1126/science.1122225
|View full text |Cite
|
Sign up to set email alerts
|

General Strategies for Nanoparticle Dispersion

Abstract: Traditionally the dispersion of particles in polymeric materials has proven difficult and frequently results in phase separation and agglomeration. We show that thermodynamically stable dispersion of nanoparticles into a polymeric liquid is enhanced for systems where the radius of gyration of the linear polymer is greater than the radius of the nanoparticle. Dispersed nanoparticles swell the linear polymer chains, resulting in a polymer radius of gyration that grows with the nanoparticle volume fraction. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

43
799
3
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 892 publications
(849 citation statements)
references
References 30 publications
43
799
3
4
Order By: Relevance
“…It has been recently proposed that a thermodynamically stable dispersion of nanoparticles without agglomeration or phase separation should be achieved when the radius of gyration, R g , of the polymer host is larger than the radius of the nanoparticles. 60 Hooper and Schweizer 16 suggested that R g is not the key variable, but rather the ratio of particle diameter to monomer (D/d) is crucial magnitude taking dense polymer-particle mixtures as a model system. This size ratio is relevant for the magnitude of particle-particle attraction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently proposed that a thermodynamically stable dispersion of nanoparticles without agglomeration or phase separation should be achieved when the radius of gyration, R g , of the polymer host is larger than the radius of the nanoparticles. 60 Hooper and Schweizer 16 suggested that R g is not the key variable, but rather the ratio of particle diameter to monomer (D/d) is crucial magnitude taking dense polymer-particle mixtures as a model system. This size ratio is relevant for the magnitude of particle-particle attraction.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our results, we show the effect of confinement on dispersibility, D, of nanoparticles as a function of size asymmetry f and fraction of inclusion f p , which would alter the reported bulk phase behaviour 4,9,11,13,15 . As a consequence of the enhanced dispersion, we observe a reduction in T g of such blends as compared with that in the bulk at comparable nanoparticle volume fractions.…”
mentioning
confidence: 99%
“…Recent studies, however, have also shown that dispersion and thermomechanical properties could be controlled using multicomponent grafted polymer chains 16 . On the other hand, very little is known or understood about the nature of dispersion of nanoparticles in thin polymer films [5][6][7]9,10,12 . This is a bit surprising since, a vast amount of research has been devoted to understanding of structure and properties of thin polymer films, especially those related to the perturbation of chain conformation [17][18][19][20][21] and glass transition due to confinement [5][6][7][8]11,[22][23][24][25] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to much excitement about the possible applications of these nanoparticles in many materials science applications. [1][2][3][4][5][6][7] Though the quantitative understanding of the mechanisms behind these property improvements is still developing, it is well accepted that the surface area of NP in contact with the polymer matrix plays a pivotal role. 2 Moreover, the amount of NP surface area in contact with polymers depends on NP dispersion, and thus the problem of ensuring a stable NP dispersion has been a preoccupation with these materials.…”
Section: Introductionmentioning
confidence: 99%